Legal Protection for E-Commerce Sellers and Consumers in Indonesia Reviewed from Law Number 8 of 1999 and Law Number 11 of 2008 - Rosari, Kristin Gaby; Subekti; Suyono, Yoyok Ucuk; Widodo, Ernu (Lex Stricta : Jurnal Ilmu Hukum, 2025)
The problem in this research is that the act of default can cause losses to the contract partner, so the contract partner who is harmed has the right to ask for legal protection through the court to force the person who committed the default to carry out his obligations in accordance with the agreed contract. The purpose of this study is to determine the type of legal protection that each party has and investigate the challenges associated with putting current regulations into effect.  The concepts of justice, legal certainty, and legal protection are examined along with pertinent laws and regulations using the normative legal method. The results of the study show that current regulations already cover various forms of protection, such as electronic contract requirements, business actors' obligations to provide transparent product information, and sanctions for violations of the law. However, the implementation of regulations faces obstacles, including lack of legal awareness and technological limitations. This study recommends strengthening government supervision, increasing digital literacy among the public, and collaboration between stakeholders to create a safer and more equitable e-commerce environment.